Baseline adjustment methodology in a shared water savings contract during severe water restrictions – a case study in the Western Cape, South Africa - HE Jacobs; JL Du Plessis; Nicole Nel; S Gugushe; S Levin (Water SA, 2020)
A novel method for baseline adjustment in a shared water savings contract under serious drought conditions was presented in a companion paper. The newly developed baseline adjustment method was subsequently applied to a case study, as discussed in this manuscript. The case study involved application of the method to 24 relatively complex sites, spread over the Western Cape Province in South Africa. The sites included, for example, military bases, naval dockyards, an airforce base, prison facilities, large multi-storey blocks of flats and administrative office buildings. Baseline adjustment became essential mid-contract during the serious water restrictions in Cape Town at the time. The restrictions were linked to the ‘Day Zero’ scenario in 2018 when water supply would potentially run out, and resulted in water savings at baseline sites that were ascribed to external factors. The study incorporated a comprehensive review of the approved baseline reports with site visits to 12 of the properties. The baseline adjustment method provided a robust means to obtain adjustments for sites with relatively limited data. The minimum data requirement was a record of monthly water consumption per site. The adjustments varied between 0% and 64% of the original baseline value for the different sites in the study sample. The relatively higher adjustments were linked to sites where outdoor irrigation and pool water use was prevalent during the baseline-setting period, but was banned during the drought. Zero adjustments were found for sites with exceptionally high leakage flows that had subsequently been repaired; leaks dwarfed actual use in these cases. The results for all 24 sites were accepted by the contracting parties as being reasonable and fair.